2022
DOI: 10.52711/0974-360x.2022.00503
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Evaluation of Novel Antidiabetic Polyherbal Formulation

Abstract: Polyherbal formulation having more than one plant in the particular dosage form. These formulation shows greater therapeutic efficacy compared to single plant. In the present study. It was intended to formulate antidiabetic polyherbal formulation incorporating different ratio of the Annona squamosa (leaves), Withania somnifera (roots), Tinospora cordifolia (stems)and Azadirachta indica (leaves). The seven different polyherbal formulation (HF1 to HF7) were prepared and administered orally to the streptozotocin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…The findings of present study are similar with the findings of others that demonstrated the substantial antihyperglycemic properties of polyherbal formulation in STZ induced diabetic rats. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Our findings are similar with the findings of other authors. It has been demonstrated that our discoveries can decrease blood sugar levels in diabetic animals.…”
Section: Body Weight Of Ratssupporting
confidence: 91%
See 1 more Smart Citation
“…The findings of present study are similar with the findings of others that demonstrated the substantial antihyperglycemic properties of polyherbal formulation in STZ induced diabetic rats. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Our findings are similar with the findings of other authors. It has been demonstrated that our discoveries can decrease blood sugar levels in diabetic animals.…”
Section: Body Weight Of Ratssupporting
confidence: 91%
“…Compared to individual natural products, each benefit has contributed to the increased popularity of polyherbal formulation on the trade. 7,8 Azadirachta indica, Tinospora cordifolia and Oscimum sanctum are medicinal plants used for centuries to heal hyperglycemia. Thus, it was intended to explore the anti-diabetic properties of a polyherbal formulation containing different ratios of A. indica leaves, T. cordifolia stem and O. sanctum leaves.…”
Section: Introductionmentioning
confidence: 99%